Rheumatoid arthritis – usage of biomarkers in disease’ prognosing, diagnosing and monitoring - Skrzynecka, Sabina; Pietruszewska, Hanna; Sędziak, Oliwia; Kruszewska, Natalia; Borucińska, Urszula (Quality in Sport, 2025)
Introduction: Rheumatoid arthritis (RA) is a chronic inflammatory joint disease which has a significant, negative influence of patients’ quality of daily life. In routine clinical practice there is a usage of classic biomarkers, such as rheumatoid factor (RF) and anti-citrullinated antibodies (anti-CCP), as well as C-reactive protein (CRP) and erythrocyte sedimentation rate (ESR) in detecting onset or exacerbation of the disease and in monitoring its course. Aim: The study presents other markers with higher sensitivity and specificity which will let doctors identify even smoldering systemic inflammation and introduce appropriate treatment to prevent serious consequences of RA, including joints’ erosion and disability. Methodology: This review was conducted using a systematic approach to identify and analyze relevant scientific literature on the potential biomarkers of RA activity and progression and to indicate their practical clinical implications. We searched PubMed and Google Scholar databases. Articles were searched using following words : “Rheumatoid arthritis”, “biomarkers”, “ inflammatory”, “progression”,” treatment”. Summary: In a group of promising markers there are: calprotectin (S100A8/S100A9), 14-3-3η, antibodies against carbamylated proteins (anti-CarP), metalloproteinase 3 (MMP-3), other MMPs and cytokines (IL-1, IL-6, TNF-α).